2014
DOI: 10.1371/journal.pntd.0003327
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome in Relation to Treatment of Murine Typhus and Scrub Typhus Infection: A Fever Cohort and a Case Series Analysis

Abstract: BackgroundThere is a paucity of published reports on pregnancy outcome following scrub and murine typhus despite these infections being leading causes of undifferentiated fever in Asia. This study aimed to relate pregnancy outcome with treatment of typhus.Methodology/Principal FindingsData were analyzed from: i) pregnant women with a diagnosis of scrub and/or murine typhus from a fever cohort studies; ii) case series of published studies in PubMed using the search terms “scrub typhus” (ST), “murine typhus” (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 49 publications
1
64
1
Order By: Relevance
“…Mane et al detected higher SFG IgM positivity in females and higher IgM seropositivity for TG rickettsiae in housewives [13]. Clinically, McGready et al reported that scrub typhus and murine typhus are indistinguishable with a poor neonatal outcome in 36% of patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Mane et al detected higher SFG IgM positivity in females and higher IgM seropositivity for TG rickettsiae in housewives [13]. Clinically, McGready et al reported that scrub typhus and murine typhus are indistinguishable with a poor neonatal outcome in 36% of patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established the impact of scrub typhus and murine typhus as causes of acute febrile illness in Thailand (Blacksell et al 2008, Thitivichianlert et al 2009, Ruang-Areerate et al 2011) and adjacent countries (Phongmany et al 2006, Chheng et al 2013, Mayxay et al 2013, McGready et al 2014). Although pathogens like Orientia tsutsugamushi and Rickettsia typhi are well described, only limited evidence is available for other zoonotic pathogens contributing to the burden of undifferentiated febrile illness.…”
Section: Introductionmentioning
confidence: 99%
“…From a series of scrub typhus in 11 pregnant women, investigators noted an abortion rate of 18% that likely resulted from circulatory impairment relating to thrombotic occlusion or coagulopathy initiated from endothelial infection with Orientia tsutsugamushi. 25 However, thrombotic occlusive events are rare in RMSF, 26 and it is more likely that hypotensive shock could led to placental ischemia and fetal loss. In our series, infection with R. rickettsii precipitated the death of the fetus in for each of the three patients infected during the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%